Kontribusi Pengetahuan, Sikap, Perilaku Terhadap Kepemilikan Jamban Sehat Pada Penduduk Perkotaan - Vera Yulyani; Nurul Aryastuti; Gunawan, Vera (Universitas Sulawesi Barat, 2022)
Ownership of healthy latrines in Indonesia is still low. This is influenced by knowledge, attitudes and behavior that are less supportive. Ownership of healthy latrines in Bandar Lampung City is still low (87%), (25.1%) people use cemplung latrines and do not have a septic tank (53.1%). The purpose of this study was to determine the relationship between knowledge, attitudes and behavior towards ownership of healthy latrines in the Pesawahan Village, Bandar Lampung City in 2021. This study was a quantitative study with a Cross Sectional design and a sample of 207 households. The sampling technique used was purposive sampling with bivariate analysis test to determine the relationship between the independent and dependent variables using the Chi Square test. The results showed that there was a relationship of knowledge p = 0.004, there was a relationship of attitude p = 0.018 and there was a relationship of behavior p = 0.043 to ownership of healthy latrines. The recommendations made are that people who still use cemplung latrines should immediately make permanent latrines in order to increase the ownership status of healthy latrines and health workers should conduct counseling and triggering in order to increase knowledge and improve the ownership status of healthy latrines.